LITERATURE Watch Implications for transplantation. Issue 4 (30th March 2013) - Upadhyay, Vaibhav; Fu, Yang‐Xin; Bromberg, Jonathan S.
Abstract : While the concept of microbes as foreign invaders has been essential in preventing illness in transplantation, recent reports in the fi eld of immunity suggest the possibility that probiotics or targeted antibiotic therapies might be helpful in promoting graft acceptance.